The Effect of Religiosity and Parenting Pattern on Adolescent Sexual Behavior through Motivation to Avoid Premarital Sexual Behavior - Mauliana Maghfiroh (Indonesian Psychological Research, 2024)
Guidance related to Sexual behavior is important for adolescents due to the high risks and potentially negative impacts of this behavior. This study to investigate the effect of religiosity and parenting pattern on sexual behavior and to test whether motivation to avoid premarital sexual behavior mediate the effect. This quantitative correlational study involved 204 adolescents living in Kebumen regency of Central Java, selected using cluster random sampling. Data were collected through questionnaires and hypothesis testing was carried out using path analysis which technically uses multiple regression analysis. The research results showed that religiosity has a significant effect on motivation to avoid premarital sexual behavior with a contribution. Meanwhile, parenting pattern does not have a significant effect on the motivation variable to avoid premarital sexual behavior, and the religiosity has a significant effect on sexual behavior.  Furthermore, parenting pattern has a significant negative effect on adolescent sexual behavior and motivation to avoid premarital sexual behavior cannot completely become an intervening variable for religiosity and parenting Pattern regarding sexual behavior. Implications of this findings are further explained.